2015
DOI: 10.18632/oncotarget.4129
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical administration of exogenous microRNA-145 as a therapy for mouse orthotopic human bladder cancer xenograft

Abstract: We previously reported that the level of microRNA (miR)-145 is attenuated in human bladder cancer cells. In this current study, we investigated whether intravesical administration of miR-145 could be a potential therapeutic strategy for controlling bladder cancer by using an orthotopic human bladder cancer xenograft model. Following transfection of 253J B-V cells with miR-145, the effects of the ectopic expression of miR-145 were examined by performing MTT, Western blotting analysis, Hoechst33342 staining, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 22 publications
2
35
0
Order By: Relevance
“…We previously reported that ectopic expression of miR-145 induces apoptosis through the downregulation of c-Myc and socs7 in bladder cancer cells [911]. We thus confirmed this effect by performing assays to evaluate apoptotic cell death in T24 and 253J B-V cells after the transfection of these cells with miR-145 or siR-KLF4.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…We previously reported that ectopic expression of miR-145 induces apoptosis through the downregulation of c-Myc and socs7 in bladder cancer cells [911]. We thus confirmed this effect by performing assays to evaluate apoptotic cell death in T24 and 253J B-V cells after the transfection of these cells with miR-145 or siR-KLF4.…”
Section: Resultssupporting
confidence: 72%
“…We have already reported that intravesical administration of exogenous miR-145 exhibits an anti-tumor effect in a human bladder cancer xenograft model [11]. We are thus now aiming to compare the efficacy of intravesical delivery of exogenous miR-145 to that of BCG in the xenografted model mice.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-145 is often down-regulated in cancer tissues and restoration of miR-145 suppressed cancer cell invasion by reversing the EMT phenotype [12,28]. MiR-145 acts as a tumor suppressor in bladder cancer [29]. However, the mechanism of miR-145 down-regulation is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Intravesical treatment of siRNA was performed as previously described [42]. Two weeks later, intravesical treatment was initiated.…”
Section: Methodsmentioning
confidence: 99%